A luta multivocal pelo direito à memória em Teófilo Otoni, Vale do Mucuri - Souza, Andrey Lopes de; Silva, Felismina Dalva Teixeira (Revista Vozes dos Vales: Publicações Acadêmicas, 2023)
Teófilo Otoni is the main city of Vale do Mucuri, a mesoregion in the Northeast of Minas Gerais. It is a space constituted by the presence of native populations, blacks, European and Eastern immigrants who arrived attracted by the proposal of a colonizing project designed for the region. Teófilo Otoni was constituted as a heterogeneous city, marked by the presence of these diverse social subjects. However, in official memory the presence of European immigrants prevails, whether in the names given to streets and avenues, buildings and monuments, or in the spatial dominance of economically valued land in the city. In this sense, the objective of this work is to problematize the official / hegemonic and alternative “places of memory”, revealing the multivocal struggle present in the disputes around projects and memories for the right to the city and to memory as a milestone of conquest of citizenship.